484PActivity of afatinib in patients (pts) with EGFR mutation-positive (EGFRm+) NSCLC and baseline brain metastases: Pooled analysis of three large phase IIIb trials. (24th November 2019) - Gottfried, M; de Marinis, F; Tu, H; Laktionov, K K; Feng, J; Poltoratskiy, A; Zhao, J; Tan, E-H; Lee, V; Kowalski, D; Yang, C-T; Srinivasa, B; et al.
Abstract: Background: In the LUX-Lung (LL) 3 and 6 trials, first-line afatinib significantly improved PFS vs chemotherapy in pts with EGFRm+ NSCLC and baseline brain mets (HR, 0.50; P = 0.03). 1 In LL7, similar PFS improvement with afatinib vs gefitinib was observed in pts with, and without, brain metastases (HR, 0.76 and 0.74; Pint =0.93). 2 Competing risk analysis of LL3/6 demonstrated low risk of de novo CNS progression in pts treated with afatinib (6%). 3 Here, we assess afatinib in pts with brain metastases treated in a 'real-world' setting. Methods: Retrospective pooled analysis of three 'real-world' studies: a multi-center expanded-access program in Korea (1200.193); an Asian phase IIIB trial (1200.66); a global phase IIIB trial (mainly Europe; 1200.55). All three studies recruited EGFR TKI-naïve pts with EGFRm+ NSCLC who received afatinib 40 mg/day, including pts with asymptomatic brain metastases. Dose reduction was permitted (minimum 20 mg/day). Endpoints included investigator-assessed progression-free survival (PFS), time to symptomatic progression (TTSP) and objective response rate (ORR). Results: A total of 1108 pts were treated with afatinib. Baseline characteristics were: median age, 61 yrs; female, 58%; ECOG PS of 0/1/2, 26%/70%/4%; uncommon EGFR mutations: 18%; first-line afatinib, 69%. In total, 213 pts had brain metastases. Median PFS and TTSP in these pts were 10.6 months (95% CI 9.1–12.8) and 13.7 months (95% CI 11.0–14.8), respectively. When restricted to pts harboring common EGFR mutations, median PFS and TTSP were 11.7 months (95% CI 10.1–13.8) and 14.4 months (95% CI 12.9–16.4), respectively. ORR was 57% (59% in pts with common EGFR mutations); median duration of response was 11.1 months (95% CI 8.3–12.3). Conclusions: Consistent with clinical trial data, afatinib is active in pts with EGFRm+ NSCLC and brain metastases treated in a real-world setting in Asian and Caucasian pts. 1. Schuler, M. et al. J Thorac Oncol 2016;11:380–90 2. Park, K. et al. Lancet Oncol 2016;17:577–89 3. Girard, N. Future Oncol. 2018;14:1117–32. Clinical trial identification: NCT01931306; NCT01953913; NCT01853826. Editorial acknowledgement: Lynn Pritchard of GeoMed, an Ashfield company, part of UDG Healthcare plc. Legal entity responsible for the study: Boehringer Ingelheim. Funding: Boehringer Ingelheim. Disclosure: F. de Marinis: Honoraria (self): Roche; Honoraria (self): AstraZeneca; Advisory / Consultancy: Takeda; Research grant / Funding (institution): Boehringer Ingelheim. V. Lee: Honoraria (self), Advisory / Consultancy: Pfizer; Honoraria (self): Eli Lilly; Honoraria (self), Advisory / Consultancy: Roche; Honoraria (self), Advisory / Consultancy: AstraZeneca; Honoraria (self), Advisory / Consultancy: Merck Sharp & Dohme. L. Clementi: Full / Part-time employment: Boehringer Ingelheim . W. Tang: Full / Part-time employment: Boehringer Ingelheim . D.C-L. Huang: Full / Part-time employment: Boehringer Ingelheim . A. Cseh: Full / Part-time employment: Boehringer Ingelheim . K. Park: Advisory / Consultancy: AMGEN; Advisory / Consultancy: Astellas; Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (self): AstraZeneca; Advisory / Consultancy: BluePrint; Advisory / Consultancy: BMS; Advisory / Consultancy, Speaker Bureau / Expert testimony: Boehringer Ingelheim; Advisory / Consultancy: Eli Lilly; Advisory / Consultancy: Hanmi; Advisory / Consultancy: KHK; Advisory / Consultancy: Loxo; Advisory / Consultancy: Merch KGaA; Advisory / Consultancy, Research grant / Funding (self): MSD; Advisory / Consultancy: ONO; Advisory / Consultancy: Roche. C. Zhou: Honoraria (self): BI; Honoraria (self): Roche; Honoraria (self): Sanofi; Honoraria (self): Hengrui; Honoraria (self): Qilu; Honoraria (self): MSD. Y-L. Wu: Honoraria (self), Advisory / Consultancy: AZ; Advisory / Consultancy, Research grant / Funding (self): Roche; Honoraria (self), Advisory / Consultancy: BMS; Full / Part-time employment: Guangdong Provincial People's Hospital, China; Honoraria (self): Eli Lilly; Honoraria (self): Pfizer; Honoraria (self), Research grant / Funding (self): BI. All other authors have declared no conflicts of interest.